Efgartigimod treatment in patients with anti-MuSK-positive myasthenia gravis in exacerbation - Shi, Fangyi; Chen, Jiaxin; Feng, Li; Lai, Rong; Zhou, Hongyan; Sun, Xunsha; Shen, Cunzhou; Feng, Jiezhen; Feng, Huiyu; Wang, Haiyan (Frontiers in Neurology, 2024)
BackgroundThe prevalence of patients positive for muscle-specific kinase antibody (hereafter, MuSK-Ab) accounts for 5–8% of all myasthenia gravis (MG) cases. Currently, efgartigimod has shown good therapeutic effects in MUSK-Ab-positive MG patients in a phase III clinical trial. However, phase III clinical trials tend to exclude MG patients in exacerbation, and there are only few real-world studies on the efficacy of efgartigimod in MuSK-Ab-positive myasthenic crisis (MC) patients. This retrospective, real-world study aimed to explore the efficacy of efgartigimod in MuSK-Ab-positive MG with exacerbation.MethodsWe reviewed the clinical data of four MuSK-Ab-positive patients with exacerbation of MG who received efgartigimod at the First Affiliated Hospital of Sun Yat-sen University, including two patients with MC. All patients were admitted between September 2023 and May 2024. Most patients are simultaneously undergoing rituximab treatment.ResultsEach patient completed one cycle of efgartigimod. After the first administration, four patients showed a clinically meaningful decrease in the Myasthenia Gravis Activities of Daily Living (MG-ADL) score (a reduction of more than 4 points compared to baseline), and all patients showed a decrease in IgG levels after one cycle of efgartigimod. Regarding safety, none of the patients experienced any obvious adverse effects. At the final follow-up, all patients achieved the minimal symptom expression status (an MG-ADL score of 0 or 1) following the first administration of efgartigimod for 8.75 ± 5.56 weeks. This article presents a case involving a patient who exhibited prompt alleviation of symptoms following the administration of a high dose of efgartigimod (20 mg/kg, given on days 1 and 5), without the use of any other fast-acting treatment.ConclusionThis retrospective real-world study demonstrates the effectiveness and safety of efgartigimod in these four MuSK-Ab-positive, female Asian patients with exacerbation of MG, as well as in patients experiencing MC. It is important to note that efgartigimod should not be viewed as a substitute for foundational immunotherapy; rather, it is intended as a rescue treatment during exacerbations and as an adjunctive therapy in the context of long-term immunotherapy. This non-invasive approach has the potential to become another treatment option for MuSK-Ab-positive MG patients.